Formulation and Evaluation of Ranolazine Extended Release Tablets by using pH Dependent and Independent polymers - Pittala, Bhargavi (International Journal of Pharmaceutical & Biological Archive, 2014)
Formulation and Evaluation of Ranolazine Extended Release Tablets by using pH Dependent and Independent polymers